1997
DOI: 10.1037/0894-4105.11.4.523
|View full text |Cite
|
Sign up to set email alerts
|

Perseverative behavior in Alzheimer's disease and subcortical ischemic vascular dementia.

Abstract: Perseverative behavior has not been extensively studied in patients with dementia. In this study, perseverative behavior was elicited with the dementia version of the Graphical Sequence Test. A control group and participants with Alzheimer's disease (AD) and subcortical ischemic vascular dementia (IVD) were studied. A factor analysis revealed a 3-factor model consisting of perseverations related to semantic knowledge, motor functioning, and a third, intermediary factor. IVD participants made more total perseve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 23 publications
5
52
0
Order By: Relevance
“…The increased number of perseverations on semantic fluency (recurrent perseverations) in AD suggests distinct patterns of perseverative behaviour in these disorders in agreement with a previous report of comparable populations [33]. Our findings are consistent with the hypothesis of perseverations proposed by Sandson and Albert [34].…”
Section: Discussionsupporting
confidence: 83%
“…The increased number of perseverations on semantic fluency (recurrent perseverations) in AD suggests distinct patterns of perseverative behaviour in these disorders in agreement with a previous report of comparable populations [33]. Our findings are consistent with the hypothesis of perseverations proposed by Sandson and Albert [34].…”
Section: Discussionsupporting
confidence: 83%
“…A first study specifically comparing graphic perseverations in patients with AD or VaD showed that perseverations were more frequent in VaD than in AD [172]. However, Cosentino et al [173] assessed patients on CDT and on copying clocks and observed that perseveration and closing-in (see below) in AD and VaD were more frequent in patients with higher number of white matter lesions and with more marked impairment on executive frontal tasks.…”
Section: Graphic Perseverationmentioning
confidence: 99%
“…number of categories on the Wisconsin Card Sorting Test and performance on Raven's Colored Progressive Matrices). Moreover, Lamar et al [19] reported a pattern of perseverative behavior in s-IVD patients different from that of AD patients. In line with the assumption that conventional neuropsychological tests might fail to distinguish between cortical and subcortical dementia, Mendez and Mendez [20] suggested unstructured tasks that require executive abilities such as behavioral initiation as the most useful to better differentiate VaD from AD patients.…”
Section: Introductionmentioning
confidence: 99%